NEUTRON WORKPLACE SPECTROMETRY (ENERGY AND DIRECTION) USING TL DETECTORS: FIRST APPROACH AND RESPONSE FUNCTIONS. Issue 1 (21st November 2017) - Radeck, D; Luszik-Bhadra, M; Haninger, T; Reginatto, M
Abstract: The response of albedo dosemeters depends on the energy and angle of the incident neutron radiation. For their use as personal dosemeters, a field-calibration factor has to be applied. The presently used single sphere method for field calibration can be extended and optimised by putting five albedo dosemeters on the surface of a polyethylene sphere and two TL cards in the centre. To investigate the potential of this extension, reference measurements and Monte Carlo calculations were performed and the fluence response of the detectors at different positions on and within the sphere was determined. Calculated response functions demonstrate that information on the energy and directional distribution of neutron fluence can be extracted with this simple set-up for unknown neutron fields.